Modelling the complexity of the foot and ankle during human locomotion: the development and validation of a multi-segment foot model using biplanar videoradiography. Issue 5 (4th April 2022) - Maharaj, Jayishni N.; Rainbow, Michael J.; Cresswell, Andrew G.; Kessler, Sarah; Konow, Nicolai; Gehring, Dominic; Lichtwark, Glen A.
Abstract: We developed and validated a multi-segment foot and ankle model for human walking and running. The model has 6-segments, and 7 degrees of freedom; motion between foot segments were constrained with a single oblique axis to enable triplanar motion [Joint Constrained (JC) model]. The accuracy of the JC model and that of a conventional model using a 6 degrees of freedom approach were assessed by comparison to segment motion determined with biplanar videoradiography. Compared to the 6-DoF model, our JC model demonstrated significantly smaller RMS differences [JC: 2.19° (1.43–2.73); 6-DoF: 3.25° (1.37–5.89)] across walking and running. The JC model is thus capable of more accurate musculoskeletal analyses and is also well suited for predictive simulations.